Statins in clinical practice - A. S. Sivkov; S. V. Paukov; V. G. Kukes; S. I. Sivkov (Кардиоваскулярная терапия и профилактика)
This review discusses statin treatment in patients with coronary heart disease (CHD), including acute coronary syndrome (ACS), based on the results of the latest clinical trials. The modern views on statin mechanisms of action are presented, including their pleiotropic effects, important for CHD and ACS treatment. Currently, the most effective and safe statin is atorvastatin.